N-acetylcysteine protects hepatocytes from hypoxia-related cell injury - Heil, Jan Ulrich; Schultze, Daniel; Schemmer, Peter; Bruns, Helge (Clinical and experimental hepatology, 2018)
Aim of the study Hepatocyte transplantation has been discussed as an alternative to liver transplantation in selected cases of acute and chronic liver failure and metabolic diseases. Immediately after infusion of hepatocytes, hypoxia-related cell injury is inevitable. N-acetylcysteine (NAC) has...
Gesehen am 23.10.2019